Letter - Andover Labour Party and Trades Council, 11 May 1926 (Andover)
1926-05-11 "Letter - Andover Labour Party and Trades Council, 11 May 1926" [g0302001.jpg], 11 May 1926, Andover Local Labour Party and Trades Council, Singleton, L. G. Local Organisation